(untitled) (Principles of Medical Toxicology, 2025)
Synopsis Author Miss Reetu Singh, Assistant Professor, Department of Pharmacy, Shri Rama Krishna College of Pharmacy, Satna, Madhya Pradesh, India Abstract Poison Control Centers provide essential toxicological expertise through 24/7 telephone consultation services that significantly reduce healthcare costs while improving patient outcomes. Organizationally, these centers maintain specialized staffing with certified Specialists in Poison Information (typically pharmacists or nurses with advanced training) supervised by medical toxicologists who provide clinical leadership and protocol development. Support personnel manage data systems, educational initiatives, and quality improvement programs. Operational protocols guide call management from initial triage through substance identification, risk assessment, management recommendations, and follow-up calls. Centers employ sophisticated electronic documentation systems and toxicological databases to support accurate, evidence-based advice across diverse exposure scenarios. Documentation captures essential elements including substance characteristics, exposure circumstances, clinical effects, interventions, recommendations, and outcomes, serving both immediate clinical needs and long-term surveillance functions. Centers contribute critical public health services through real-time toxicosurveillance detecting emerging threats like novel recreational drugs, medication tampering, or chemical incidents. Educational outreach targets healthcare providers, public safety personnel, and community members with poison prevention messaging and clinical toxicology updates. Research activities analyze exposure patterns, intervention efficacy, and economic impacts. Through these integrated functions, Poison Control Centers serve as sentinel systems for toxic exposures while providing cost-effective consultation that reduces unnecessary emergency department visits and improves poisoning outcomes across diverse populations. Keywords: Poison Control Centers, toxicosurveillance, Specialists in Poison Information, telephone consultation, poison prevention, National Poison Data System VIEW PDF